(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Immunotherapy is an innovative method of cancer treatment. It is based on interference in the interaction of the patient’s immune system and a malignant tumor. Immunotherapy goes well with classical methods of treatment [Ivanisova D.N., 2022]. The results of the analysis of literature data on the use of immunomodulators in the complex treatment of cancer patients with colon cancer during chemotherapy are presented.